PENGEMBANGAN PRODUKSI PESTISIDA ALAMI DARI Beauveria bassianaDAN Trichoderma sp. MENUJU PERTANIAN ORGANIK - Purnama, Herry; Hidayati, Nur; Setyowati, Eni (WARTA, 2015)
Recently the condition of agriculture in Indonesia needs to be addressed. Soil fertility getting damaged due to chemical fertilizer that is not impartial. In addition, the impact of excessive use of synthetic pesticides can cause damage to the ecosystem. Control of plant diseases using biological agents began getting attention because of public concerns due to the use of synthetic chemical pesticides. Biological agents are microorganisms,  both  naturally  occurring  such  as  bacteria,  fungi,  viruses  and protozoa, as well as the results of genetic engineering that are used to control plantpests. Madrasah Diniyah Jumapolo, Karanganyar, has pioneered the manufacture of biological agents to support organic farming although on a small scale. Community service activities undertaken to provide assistance in the improvement of the production process  and  management  improvements.  The  technology  developed  is  the  use  ofbiological pesticides agent isolated from Beauveria bassiana and Trichoderma sp. As a natural insecticide and fungicide. The activities received support from the madrasa and expressed successfully produce biological agents in the proper packaging. In addition to the consumption of madrasa and nearby farmers, pesticide product ofbiological agents is also sold to the public. The selling of products will increase the development of organic farming to produce healthy food also will gain additional income for the madrasa.